America's allies and the decline of US hegemony - Massie, Justin; Paquin, Jonathan, 1975- (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Using the case-studies of Europe, the UK, Australia, Canada, Japan and South East Asian countries, this book offers a broad assessment of the perceptions of threat and the strategies used by these allies to cope with the relative decline of America's hegemonic power, the rise of China and the transforming world order"--
Introduction : America's allies coping with US relative decline / Justin Massie and Jonathan Paquin -- American decline : destined, chosen, or contingent? / Robert J. Lieber -- China's counter-hegemony? : evidence from 'making identity count' / Srdjan Vucetic -- China's relations with US Pacific Rim allies : tensions between Trump's 'America first' and Chinese 'sharp power' / Steven F. Jackson -- Japanese national security policy : balancing, but hedging / Clifton Sherrill -- Australia's role conceptions in a multipolar world / Cameron G. Thies -- Power transition and traditional allies in Southeast Asia / Ralf Emmers -- Canada's middle power ambivalence : the palimpsest of US power under the Chinese shado / Jeremy Paltiel -- The fraying transatlantic order and Europe's struggle in a multipolar world / Riccardo Alcaro -- NATO in crisis : vanishing leadership and distracted allies / Trine Flockhart -- The European Union's evolving role in response to US waning hegemony / Simon Schunz and Brice Didier -- Making sense of the future : European discourse on global power transition / Caterina Carta -- Conclusion : allies and the fate of U.S. hegemony / Justin Massie and Jonathan Paquin.
OCLC-licensed vendor bibliographic record.
Keywords: Hegemony -- United States; World politics -- 21st century; United States -- Foreign relations -- 21st century; POLITICAL SCIENCE / General; POLITICAL SCIENCE / International Relations / General